Innovation Strategy for Civil Servant HR Development in the Digitalization Era: BPSDMD Banten Province - Defi Nuryadin; Feri Fadli Rizki; Lufki Lufki (HK-Publishing, 2025)
Local governments are required to adapt to electronic systems through the Electronic-Based Government System (SPBE) policy. The Human Resources Development Agency (BPSDMD) of Banten Province faces challenges such as low digital literacy among civil servants, a conventional work culture, and limited network infrastructure. This study aims to evaluate the effectiveness of innovation strategies for civil servant human resource development in addressing these challenges, utilizing Chandler’s strategy theory and Bekkers’ digitalization framework. A descriptive qualitative approach was employed, involving interviews, observations, and document analysis. The results indicate that BPSDMD Banten Province successfully implemented blended learning and distance learning methods, while optimizing the